Methods and Tips for Teaching English to Primary School Children (Eurasian Research Bulletin, 2023)
The article considers methods of teaching English language for primary school children, the importance of songs during class, why tasks that require creativity should be part of the lessons, why it is necessary to add critical reading to the lessons, the importance of story times, why routine is necessary, the benefits of using flashcards, the importance of breaks during class, and why teachers should enjoy working with young children